(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
In this article, the positive value of museum pedagogy, the history of its origin, and the importance of educating future teachers in the spirit of patriotism, along with pedagogical technologies in the educational system, as a factor that determines the development of the society, the effectiveness of the educational system considered.